Meiotic and developmental competence of growing pig oocytes derived from small antral follicles is enhanced in culture medium containing FGF2, LIF, and IGF1 (FLI medium) - Bartková, Alexandra Rosenbaum; Němcová, Lucie; Kinterová, Veronika; Radová, Dominika; Strejček, František; Toralová, Tereza; Laurinčík, Jozef; Procházka, Radek (Journal of ovarian research, 2024)
BACKGROUND: Oocytes of large animal species isolated from small ovarian follicles (< 2 mm) are less competent to support early embryonic development after in vitro maturation and fertilization than their counterparts isolated from medium-sized and preovulatory follicles. This study aimed to assess the effect of a new maturation medium containing FGF2, LIF, and IGF1 (FLI medium) on the meiotic and developmental competence of pig cumulus-oocytes complexes (COCs) derived from the small and medium-sized follicles. METHODS: The growing oocytes were isolated from 1 to 2 (small follicle; SF) and the fully-grown ones from 3 to 6 (large follicle; LF) mm follicles and matured in a control M199 medium with gonadotropins and EGF and the FLI medium enriched by the triplet of growth factors. The matured oocytes were parthenogenetically activated and cultured to the blastocyst stage. Chromatin configuration before and during the culture and MAP kinase activity were assessed in the oocytes. Finally, the expression of cumulus cell genes previously identified as markers of oocyte quality was assessed. RESULTS: The maturation and blastocyst rates of oocytes gained from LF were significantly higher than that from SF in the control medium. In contrast, similar proportions of oocytes from LF and SF completed meiosis and developed to blastocysts when cultured in FLI. Most of the oocytes freshly isolated from SF possessed germinal vesicles with fine filaments of chromatin (GV0) or chromatin surrounding the nucleolus (GVI; 30%); the oocytes from LF were mainly in GVI (or GVII) exhibiting a few small lumps of chromatin beneath the nuclear membrane. When cultured in the FLI medium for 16 h, an acceleration of the course of maturation in oocytes both from SF and LF compared to the control medium was observed and a remarkable synchrony in the course of chromatin remodeling was noticed in oocytes from SF and LF. CONCLUSIONS: This work demonstrates that the enrichment of culture medium by FGF2, LIF, and IGF1 can enhance the meiotic and developmental competence of not only fully-grown, but also growing pig oocytes and significantly thus expanding the number of oocytes available for various assisted reproductive technology applications.
Keywords: Animals; Female; Gene expression; Meiosis; IVM techniky; ženské pohlaví; meióza; Chromatin; Fibroblast Growth Factor 2; Follicle size; Oocytes; ovariální folikul; Growth factors; těhotenství; prasata; oocyty; fibroblastový růstový faktor 2; In Vitro Oocyte Maturation Techniques; Oocyte maturation; Developmental potential; Swine; chromatin; MAPK activation; zvířata; Ovarian Follicle; Pregnancy; Chromatin configuration